Optimal load setting provides higher peak power and fatigue index with a similar mean power during 30-s Wingate anaerobic test in physically active men. Issue 4 (2nd October 2021) - Silveira-Rodrigues, João Gabriel; Maia-Lima, André; Almeida, Pedro Augusto Santos; França, Bárbara Marielle Silva; Campos, Bruno Teobaldo; Penna, Eduardo Macedo; Gordon, Dan; Prado, Luciano Sales
ABSTRACT: Background : The Wingate test is usually conducted using resistance loads of 7.5, 8.5 or 8.7 g.kg −1 of body mass. However, these cycle ergometer resistance loads may be insufficient to enable maximal power values. As such, the use of individual optimal load selection (OPT) can positively influence other Wingate test parameters. Moreover, anthropometric parameters, e.g. body mass index, may also affect the OPT, but have not been well investigated. Aim: To investigate (i) individual OPT on the Wingate Test for peak power (PP), mean power outputs (MP), and the fatigue index (FI) and (ii) the association between OPT and anthropometric parameters. Methods: Fifteen physically active men (age = 26.4 ± 4.1 yr) performed six 30-s Wingate tests, with loads corresponding to 6.5%, 8.5%, 10.5% 11.5% 12.5%, and 13.5% of body mass to determine OPT (the load corresponding with the highest peak power), and also PP, MP, and FI. Results: Peak Power was 15% higher ( p <0.001) and FI was 21% higher ( p =0.03) for the OPT method, whereas Mean Power values were similar between OPT and the 8.5% of body mass load. The 8.5% of body mass resistance load underestimates power outputs and is directly related to individual Peak Power ( r =0.58, p =0.02). Furthermore, the load corresponding to OPT was inversely correlated to body mass index ( r =−0.81, p <0.001) and percent body fat ( r =−0.51, p =0.04). Conclusion: Optimal load selection is more appropriate than the use of 8.5% of body mass load to enable higher Peak power in the 30-s Wingate test in a physically active male population.